A deglacial record of carbon release from thawing permafrost of the European tundra (EUROTHAW), Marine carbon production, export, relocation and degradation under varying ocean redox conditions off NW Africa (MACPEI), Cruise No. MSM 79, October 29 - November 9 - December 3, 2018, Edinburgh (UK) - Las Palmas (Spain) - Mindelo (Cape Verde) ... - Zonneveld, Karin; Baumann, Karl-Heinz; Boersen, Barry; Bösche, Janina; Decker, Charlotte; De Visser, Jan-Dirk; Donner, Barbara; Elvert, Marcus; Fischer, Gerhard; Grotheer, Hendrik; Kattein, Laura; Klann, Marco; et al. (Gutachterpanel Forschungsschiffe, 2019)
MARIA S. MERIAN-Berichte ...